Biogeographic patterns of planktonic and meiobenthic fauna diversity in inland waters of the Russian Arctic. (11th October 2020) - Fefilova, Elena; Dubovskaya, Olga; Frolova, Larisa; Abramova, Ekaterina; Kononova, Olga; Nigamatzyanova, Gulnara; Zuev, Ivan; Kochanova, Elena
Abstract: Broad‐scale assessment of biodiversity is needed for detection of future changes across substantial regions of the Arctic. Presently, there are large data and information gaps in species composition and richness of the freshwater planktonic and meiobenthos communities of the Russian Arctic. Analysis of these data is very important for identifying the spatial distribution and temporal changes in species richness and diversity of rotifers, cladocerans, and copepods in the continental Russian Arctic. We investigated biogeographic patterns of freshwater plankton and meiobenthos from c . 67° to 73°N by analysing data over the period 1960–2017. These data include information on the composition of rotifers, cladocerans, and copepods obtained from planktonic and meiobenthic samples, as well as from subfossil remains in bottom sediments of seven regions from the Kola Peninsula in the west, to the Indigirka River Basin (east Siberia) in the east. Total richness included 175 species comprised of 49 rotifer genera, 81 species from 40 cladoceran genera, and 101 species from 42 genera of calanoid, cyclopoid, and harpacticoid copepods. Longitudinal trends in rotifer and micro‐crustacean diversity were revealed by change in species composition from Europe to eastern Siberia. The most common and widespread species were 19 ubiquitous taxa that included Kellicottia longispina (Rotifera), Chydorus sphaericus s. lat. (Cladocera), Heterocope borealis, Acanthocyclops vernalis, and Moraria duthiei (Copepoda). The highest number of rare species was recorded in the well‐studied region of the Bolshezemelskaya tundra and in the Putorana Plateau. The total number of copepod and rotifer species in both Arctic lakes and ponds tended to increase with latitude. Relative species richness of copepods was positively associated with waterbody area, elevation, and precipitation, while relative species richness of cladocerans was positively related to temperature. This result is consistent with known thermophilic characteristics of cladocerans and the cold tolerance properties of copepods, with the former being dominant in shallow, warmer waterbodies of some western regions, and the latter being dominant in large cold lakes and waterbodies of eastern regions. Rotifers showed a negative association with these factors. Alpha‐ and β‐diversity of zooplankton in the Russian Arctic were strongly related to waterbody type. Lake zooplankton communities were more diverse than those in pond and pool systems. Moreover, the highest β‐diversity values were observed in regions that showed a greater breadth in latitude and highly heterogeneous environmental conditions and waterbody types (Bolshezemelskaya tundra and Putorana Plateau). Redistribution of freshwater micro‐fauna caused by human activities occurred in the 1990s and 2000s. As a result of climate warming, a few cladoceran species appear to have extended their range northward. Nevertheless, the rotifer and micro‐crustacean fauna composition and diversity of the majority of Arctic regions generally remain temporally conservative, and spatial differences in composition and species richness are chiefly associated with the differences between the warmer European and colder east Siberian climates.